Influence of Satlogi Santri Values on Sufistic Leadership: Enhancing Service Quality and Productivity in Pesantren - Fauzi, Ahmad; Dakir, Dakir; Qodir, Abdul; Fatchurahman, M; Minarti, Sri (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the influence of satlogi santri values on the development of Sufistic leadership at Pesantren Zainul Hasan Genggong Probolinggo, with a particular focus on their impact on service quality and individual productivity. Adopting a qualitative design, data were gathered through interviews, observations, and documentation. The findings indicate that the habitualization process occurs in three stages: externalization, in which values are articulated and transmitted by pesantren leaders; objectivation, in which these values are institutionalized through daily practices and rituals; and internalization, in which values such as humility, sincerity, and integrity become embedded in leaders’ behaviors. This process fosters a leadership style that emphasizes ethical conduct, exemplarity, and accountability. As a result, Sufistic leadership improves communication, strengthens trust, enhances service quality, and promotes a productive work culture. The study concludes that Sufistic leadership provides not only a solution to the ethical leadership crisis in educational institutions but also a practical framework for pesantren and other Islamic educational settings to cultivate sustainable organizational culture and improve overall institutional effectiveness.